Precise measurement of the top-quark mass in the lepton+jets topology at CDF II - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We present a measurement of the mass of the top quark from proton-antiproton collisions recorded at the CDF experiment in Run II of the Fermilab Tevatron. We analyze events from the single lepton plus jets final state (tt̄→W+bW-b̄→lνbqq̄′b̄). The top-quark mass is extracted using a direct calculation of the probability density that each event corresponds to the tt̄ final state. The probability is a function of both the mass of the top quark and the energy scale of the calorimeter jets, which is constrained in situ by the hadronic W boson mass. Using 167 events observed in 955pb-1 of integrated luminosity, we achieve the single most precise measurement of the top-quark mass, 170.8±2.2(stat.) ±1.4(syst.)GeV/c2. © 2007 The American Physical Society.